Vulnerability and Transformation of Indonesian Peatlands - Mizuno, Kosuke; Kozan, Osamu; Gunawan, Haris (Global Environmental Studies, 2023)
This open access book deals with restoring degraded peatlands to help mitigate global warming, to which SDG 15 and SDG 13 are directly related. The book analyzes peatland degradation and restoration of the Indonesian peatland ecosystem through the integrated lens of resilience, vulnerability, adaptation, and transformation. It sheds light on what constitutes "resilience" of the peat swamp forest, digs deeper into local knowledge in developing the studies on institutions, governance, and ecological conditions that support the resilience of the peat swamp forest to elaborate on the idea of transformation in today's degraded peatlands. While peat swamp forests may be resilient, they remain highly vulnerable. The book analyzes restoration efforts through rewetting, revegetation, and rehabilitation of the local livelihoods with the concepts of adaptation and transformation. The integrated analysis covers fieldwork of more than a decade and various aspects such as agrarian and social changes, biological changes (birds, mammals, and termites), carbon emission, water control, timber use, revegetation efforts, and the Indonesia Sustainable Palm Oil (ISPO) program implementation. It also employs the ideas of vulnerability, resilience, adaptability, and transformation based on expanded studies on peatlands and observations of and participation in multiple efforts to prevent fires and restore the degraded peatland by researchers, the government, non-government organizations (NGOs), private companies, and last but not least, the local people. The discussion includes the period of pre-degradation and several efforts at peatland restoration for a better understanding and analysis of the long-term peatland dynamics.